Microsomal triglyceride transfer protein -493T variant reduces IDL plus LDL apoB production and the plasma concentration of large LDL particles. - Lundahl, B; Skoglund-Andersson, C; Caslake, M; Bedford, D; Stewart, P; Hamsten, A; Packard, C; Karpe, F (2006)
The microsomal triglyceride transfer protein (MTP) is essential for the synthesis and secretion of apolipoprotein B (apoB)-containing lipoproteins. We investigated the role the MTP -493G/T gene polymorphism in determining the apoB-100 secretion pattern and LDL heterogeneity in healthy human subjects. Groups of carriers of the T and the G variants (n = 6 each) were recruited from a cohort of healthy 50-yr-old men. Kinetic studies were performed by endogenous [(2)H(3)]leucine labeling of apoB and subsequent quantification of the stable isotope incorporation. apoB production rates, metabolic conversions, and eliminations were calculated by multicompartmental modeling (SAAM-II). LDL subfraction distribution was analyzed in the entire cohort (n = 377). Carriers of the MTP -493T allele had lower plasma LDL apoB and lower concentration of large LDL particles [LDL-I: 136 +/- 57 (TT) vs. 175 +/- 55 (GG) mg/l, P < 0.01]. Kinetic modeling suggested that MTP -493T homozygotes had a 60% lower direct production rate of intermediate-density lipoprotein (IDL) plus LDL compared with homozygotes for the G allele (P < 0.05). No differences were seen in production rates of large and small VLDL, nor were there any differences in metabolic conversion or elimination rates of apoB between the genotype groups. This study shows that a polymorphism in the MTP gene affects the spectrum of endogenous apoB-containing lipoprotein particles produced in humans. Reduced direct production of LDL plus IDL appears to be related to lower plasma concentrations of large LDL particles.